Dataset of spectroscopic, crystallography and DFT of novel 1,2-bis[N,N’-6-(4-pyridylmethylamido)pyridyl-2-carboxyamido]butane - M.A. Kadir; N.S.H. Haris; M.S.M. Yusof; K. Kassim; Fazira Ilyana Abdul Razak (Data in Brief, 2023)
This paper provided the dataset obtained from spectroscopic, crystallography and DFT of a new compound namely 1,2-bis[N,N’-6-(4-pyridylmethylamido)pyridyl-2-carboxyamido]butane. This compound is prepared from the reaction between N-6-[(4-pyridylmethylamino)carbonyl]-pyridine-2-carboxylic acid methyl ester with butane-1,4-diamine. The preparation of this compound is modified from the method described in our article [1]. In this work, we present data characterization of 1,2-bis[N,N’-6-(4-pyridylmethylamido)pyridyl-2-carboxyamido]butane from Fourier Transform Infrared (FTIR), 1H Nuclear Magnetic Resonance (1 H NMR), NOESY NMR, 13C Nuclear Magnetic Resonance (13C NMR), and elemental analysis (CHNS). The structure of this molecule is also analysed by X-ray crystallography and DFT studies. A single-crystal X-ray diffraction investigation was carried out by using Bruker SMART Apex II Duo CCD area-detector diffractometers with MoKα radiation (wavelength of λ = 0.71073 Å). The optimized energy was indicated with GaussView 5.0 and Gaussian 16 software package programme.